ELECTRIC REGULATOR WITH SOLID FILLER AND THERMOELECTRIC HEAT EXCHANGER MODULE TO PRODUCE ENERGY OF WATER-ICE PHASE TRANSITION - Ershova, Irina; Vasilyev, Alexey; Samarin, Gennady; Tikhomirov, Dmitry; Ukhanova, Viktoria; Kokunova, Irina; Dvoretckii, Leonid (Revista Inclusiones, 2019)
The authors have developed electric regulators with solid filler and thermoelectric heat exchanger module to obtain the energy of the water-ice phase transition. They substantiated that the use of the thermoelectric module provides regulator operation for potato storage heating and cooling. At that, during the change of potato storage operating modes by changing the polarity of the thermoelectric module, the speed of the regulatory body is ensured. The heating efficiency of the electric regulator with solid filler and thermoelectric module is higher than the heating efficiency of the electric regulator with solid filler and electric heater.